Q beta RNA bacteriophage: mapping cis-acting elements within an RNA genome. - Mills, D R (1990)
We have identified, for the first time, regions of cis-acting RNA elements within the bacteriophage Q beta replicase cistron by analyzing the infectivities of 76 replicase gene mutant phages in the presence of a helper replicase. Two separate classes of mutant Q beta phage genomes (35 different insertion mutants, each containing an insertion of 3 to 15 nucleotides within the replicase gene, and 41 deletion genomes, each having from 15 to 935 nucleotides deleted from different regions of the gene) were constructed, and their corresponding RNAs were tested for the ability to direct the formation of progeny virus particles. Each mutant phage was tested for plaque formation in an Escherichia coli (F+) host strain that supplied helper Q beta replicase in trans from a plasmid DNA. Of the 76 mutant genomes, 34% were able to direct virus production at or close to wild-type levels (with plaque yield ratios of greater than 0.5), another 36% also produced virus particles, but at much lower levels than those of wild-type virus (with plaque yield ratios of less than 0.05), and the remaining 30% produced no virus at all. From these data, we have been able to define regions within the Q beta replicase gene that contain functional cis-acting RNA elements and further correlate them with regions of RNA that are solely required to code for functional RNA polymerase.